Extraction and Recovery of Palladium from Aqueous Solutions

The amidoxime substituent fiber adsorbs Pd ions in the acidic solution, and the protonation in the acidic environment is used to form negative charge adsorption of PdCl4 anions, which solves the problem of ineffective adsorption of Pd in ​​the acidic solution in the prior art, and achieves high efficiency and economical Pd recycling effect.

CN112897621BActive Publication Date: 2024-12-13LCW SUPERCRITICAL TECH CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN201911362884.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-19
Filing Date
2019-12-26
Publication Date
2024-12-13
Estimated Expiration
2039-12-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively adsorb and recover palladium (Pd) metal ions in acidic solutions, especially in industrial wastewater, and the existing fibers protonate and repel positively charged metal ions in acidic environments, resulting in Ineffective adsorption.

Method used

Using polymer fibers with amide oxime substituents, Pd ions are adsorbed in acidic aqueous solution, Pd is recovered through the elution process of HCl-thiourea solution, and the amide oxime group is protonated at low pH to form negatively charged adsorbed PdCl4 anion miscombination improves adsorption efficiency and recovery efficiency.

Benefits of technology

It realizes efficient adsorption and rapid recovery of Pd in ​​acidic solution. The Pd loading of fibers is greater than 95%, and the adsorption capacity is maintained at nearly 100% in multiple cycles, reducing the cost and environmental impact of Pd recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112897621B_ABST
    Figure CN112897621B_ABST
Patent Text Reader

Abstract

The present invention relates to the extraction of platinum group elements (e.g., palladium (Pd)) by adsorption from acidic aqueous solutions using chelated acrylic fibers having amide oxime substituents, followed by recovery by elution with HCl-thiourea solution. About 10% to 100% of the acrylic fiber CN is converted to amide oxime by reaction with NH2OH (hydroxylamine) in H2O / MeOH solution in the range of 30°C to 90°C for 15 minutes to 72 hours. In multiple adsorption / elution cycles, the elements are adsorbed and loaded onto the fiber and the elution efficiency is substantially 100%. The novel fiber / extraction method is rapid, making it suitable for continuous recovery operations. A portion of the CN groups can be converted to carboxylate groups by reaction with NaOH. Short length fibers are loaded into a vertical column and a mother liquor is introduced. Upon penetration, the multiple fibers can be eluted, washed, and recycled hundreds of times without removal from the column.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the extraction of palladium (Pd) by adsorption from aqueous solution, and more particularly, to the extraction of Pd by adsorption from acidic aqueous solution using polymer fibers having amidoxime substituents, and optionally carboxyl and amidoxime substituents, followed by recovery of Pd by elution with HCl-thiourea solution. Preferred fibers are acrylic or polyacrylonitrile fibers, at least a portion of the CN groups of which have been converted to amidoxime groups. Adsorption is rapid and recovery by elution is efficient. Background Art

[0002] Fibers have been used to adsorb metal ions from near-neutral pH solutions, especially polymer fibers such as polyethylene and acrylic fibers, the acrylic fibers including substituted carboxylate groups, amide oxime groups and ester groups thereon. For example, US 10,391,472 (08-27-2019) uses polyolefin fibers having halogen atoms and vinyl addition polymer grafts covalently attached to the surface thereof, the polymer grafts being functionalized with carboxylate groups, hydroxyl groups, ketone groups, aldehyde groups, amine groups, imine groups, nitrile groups, amide groups, oxime amide oxime groups, imide dioxime groups and hydrooxalamic acid ester groups to adsorb U from U-spiked seawater. U.S. Patent Application Publication No. US2-17 / 0355621 (Dec. 14, 2019) discloses the use of acrylic polymers with mono(non-polymeric) carboxyl, amide oxime, and ester substituents to adsorb U from seawater, followed by stripping with KHCO3 or weak HCl.

[0003] However, it is not effective to adsorb metal ions from acid solutions by such types of fibers. Without being bound by theory, it is believed that the amidoxime substituent becomes protonated in acidic solutions, repels positively charged metal ions, and therefore no effective adsorption occurs. Therefore, the adsorption of such types of fibers is carried out in a near-neutral aqueous solution such as seawater, and the adsorbed metal ions are effectively extracted and recovered by using dilute HCl elution. For example, the Cu2+ ions in a near-neutral pH aqueous solution are effectively extracted by fibers containing amidoxime (and other substituents or polymeric grafts), and the adsorbed Cu ions can be eluted from fibers using dilute HCl solutions (such as 0.1M HCl). However, Cu ions are not adsorbed by such types of fibers from acid solutions because Cu2+ has a very small or non-existent K4 (formation constant of metal chloride complexes).

[0004] Recovering Pd from industrial waste presents particular problems. For example, Pd is widely used as a catalyst in many industrial-scale chemical processes, including electroless copper plating on printed circuit boards (PCBs). Effective recovery of Pd from wastewater containing low levels (about 5 to 10 ppm or less) of Pd is generally difficult to achieve. Using solid adsorbents to remove low levels of Pd from water requires a large distribution coefficient (Kd), such as an adsorbent concentration factor.

[0005] In the Cu electroplating process, Pd is used as an adjuvant for the acidic electroplating solution to increase the proportion and coverage integrity of copper. The electroplating solution usually contains 25ppm or more of Pd. The rinse water contains about 2ppm or less of Pd, but is not recovered due to technical difficulties and economic considerations. Therefore, even if the rinse water is a pollutant, it is usually thrown away. Pd is the most expensive precious metal, currently exceeding $1600 to $1700 per ounce, that is, about $5×104 per kilogram, and therefore its disposal without recovery from the electroplating process is a major processing cost. Pd is also used in the electrodeless Ni electroplating process.

[0006] Pd is also present in spent nuclear reactor fuel, but none of the existing nuclear reprocessing facilities are equipped to extract Pd from radioactive waste. Pd is also used in automotive catalytic converters, and is not usually extracted from waste. Pd is a versatile heterogeneous catalyst that is used in a variety of industrial processes, such as hydrogenation, dehydrogenation and petroleum cracking, carbon-carbon and carbon-fluorine bonding reactions in organic chemistry, as an electrocatalyst for oxidation of primary alcohols, and in platinum-type printing processes using Pd salts. Its use in synthetic biology is growing, such as in vivo catalytic activity for treating disease. However, toxicity has not been well studied and higher toxicity at the cellular level has been shown in the kidney and liver over a long period of time.

[0007] The recovery of palladium from industrial wastewater discharged from industrial plants using palladium catalysts continues to be an important economic issue due to its high value. Therefore, there is a long-standing unmet need for a rapid, efficient and inexpensive method for the adsorptive removal of Pd from such industrial, biological and municipal wastewaters, and for the recovery of Pd by a simple recovery process that allows the reuse of the adsorption medium. Summary of the invention

[0008] Unexpectedly, it has been found that Pd behaves differently from Cu and other transition metals when interacting with chelated amidoxime-containing fibers. Unlike Cu ions, Pd ions in acidic (HCl) aqueous solutions can be effectively adsorbed by amidoxime-containing fibers. Without being bound by theory, it is believed that this is due to the formation of a chloride anion complex (PdCl4) by Pd in ​​acid solutions. 2-At the same time, the amidoxime group is protonated at low pH, and the resulting amidoxime + charge attracts the negatively charged (PdCl4) 2- anionic complex, resulting in efficient adsorption on the substituted fibers.

[0009] In addition, it has been found that the protonation of the amidoxime group at low pH causes the fiber to become hydrophilic in an acid solution. Therefore, the fiber does not need conventional hydrophilic functional groups, such as carboxylate groups to effectively adsorb metal ions in an acid solution, but may include them as appropriate. Another result is that in the absence of carboxylation, a greater number or percentage of nitrile groups can be converted into amidoxime groups, rather than distributing substituents between carboxylate and amidoxime. The percentage increase of the amidoxime groups in the substituted fiber causes a greater loading of adsorbed Pd and therefore produces a greater elution yield. The number or percentage of nitrile groups that contribute to fiber strength can be controlled to provide any desired amount of fiber use stability. Another result is that the inventive adsorption fiber used in the method for the present application is not too expensive to manufacture because the carboxylation step is omitted.

[0010] The inventive amidoxime-containing fibers used in the methods of the present application are prepared from acrylic fibers such as Orlon yarns, such as by converting some of the pendant nitrile groups (-C≡N) of Orion into direct monomeric (as distinct from pendant polymeric) amidoxime groups:

[0011]

[0012] Wherein n is 1000 to 100,000, and R is alkyl, substituted alkyl, cycloalkyl, heterocycloalkyl, aryl or heteroalkyl, and the percentage of nitrile groups converted to amide oxime groups is in the range of 10% to 100%. The reaction of the acrylic fiber with hydroxylamine is maintained in methanol-water at a temperature range of about 30°C to about 90°C at a selected reaction time in the range of about 15 minutes to about 72 hours. The amide oximation reaction can also be carried out in water alone, but it is not as effective as in a methanol-water mixture. The percentage of remaining nitrile and ester functional groups can be selected to provide the desired level of mechanical properties of the resulting chelated absorbent fiber.

[0013] The resulting prepared chelating fiber containing amidoxime groups is then immersed in an acidic HCl aqueous solution containing Pd (referred to as the "pregnant solution") and exposed thereto for a suitable period of time, depleting the Pd in ​​the pregnant solution and converting it into a "barren solution", which is referred to as the "loaded fiber". Thereafter, the Pd is eluted from the loaded fiber using an HCl-thiourea solution (referred to as the "removal solution"). Rapid elution, completed in a period of time of less than about 20 minutes, produces a solution containing recovered Pd, referred to as the "recovery solution". After elution, the fiber is cleaned by rinsing with deionized water to remove the thiourea, and the resulting cleaned fiber can be reused repeatedly in multiple cycles with virtually no detectable loss of Pd adsorption capacity. The loading capacity of the amidoxime-substituted fiber is greater than 95%, and even after multiple cycles, the fiber loading capacity is close to 100%. The recovery solution can be further processed to enrich Pd therein, or it can be removed from the recovery solution as a slurry, solid precipitate, or ionic solution.

[0014] An exemplary convenient form of the fiber group to be exposed to the acidic aqueous HCl solution containing Pd to achieve adsorption is in the form of a "whisker", brush or mop, which is formed by looping the fibers through a backbone strip of polyethylene and then cutting the loops to provide a fiber tendril (string) of about 2 cm to about 10 cm in length. The backbone strip provides a holder that can be immersed in the solution used in the adsorption step. In an alternative embodiment, the fibers can be cut or chopped into short lengths, about the inner diameter of the column, inserted into the column held between upper and lower grids or glass wool plugs, and the mother liquor is pumped into the column until penetration. The loaded fibers can be retained in the column for elution and rinsing steps or they can be removed from the column and eluted. Thus, any convenient form of the chelating fiber can be used for effective exposure to the mother liquor. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 To show the relationship between the aqueous acetamide oxime in ppm and pH at 25°C 1 Pattern of H NMR shifts;

[0016] Figure 2 is a graph showing the (PdCl4)2- adsorption rate of the inventive amide oxime-containing fiber;

[0017] Figure 3 is a graph showing the rate of elution of Pd from an inventive amide oxime-containing fiber using an HCl-thiourea solution;

[0018] Figure 4 Graph showing the Pd loading capacity of inventive amide oxime-containing fibers after multiple exposure cycles;

[0019] Figure 5 A graph showing the ability to extract palladium from an acid solution (500 ppb pd2+ at pH=1) by an amide oxime-containing fiber (Example 1) and an amide oxime-carboxylate-containing fiber (Example 2); and

[0020] Figure 6 Graph showing the ability of palladium to be extracted from an acid solution (20 ppm pd2+ at pH=1) by amide oxime-containing fiber (Example 1) and amide oxime-carboxylate-containing fiber (Example 2). DETAILED DESCRIPTION

[0021] The following embodiments illustrate the present invention by way of example, but are not intended to limit the scope, equivalents, or principles of the present invention. This specification will clearly enable one skilled in the art to make and use the present invention, and describes several specific examples, modifications, variations, alternatives, and uses of the present invention. Each publication, patent, and patent application publication cited in this specification is incorporated herein by reference.

[0022] Figure 1 For aqueous acetamide oxime in aqueous solution 1 The H NMR shift pattern. The curve passes through a pair of inflection points as the acidity decreases. a Point (1) and pK a (2) identification, 13.21 and 5.78 respectively. In the pH region below (2), acetamide oxime is protonated by connecting H to the hydroxylated nitrogen atom, in the form shown above the figure. In the intermediate pH region between (2) and (1), acetamide oxime is neutral, that is, no longer protonated, as shown in the structural formula above the figure. In the pH region above (1), acetamide oxime is now negatively charged due to the loss of hydroxyl hydrogen. This indicates that in acidic solution, amide oxime will be positively charged and able to hydrogen bond to negatively charged metal ions or complexes. In contrast, in alkaline solution, negatively charged amide oxime will not bond to negatively charged metal ions or complexes, and will actually repel them. In the intermediate region, neutral pH, there is no charge and therefore any extraction is carried out by accidental physical retention. In fact, above pH 6, Pd forms a precipitate in the form of Pd(OH)2.

[0023] Example:

[0024] Example 1, Preparation of test fibers (A-fibers): The nitrile groups of Orion acrylic fibers were converted to amide oxime groups by treating the fibers with 3% by weight NH2OH (hydroxylamine) in a 1:1 (v / v) H2O / MeOH solution at a temperature ranging from 30°C to 90°C for 15 minutes to 72 hours. The percentage of nitrile groups converted to chelated amide oxime groups can be controlled to vary between about 10% and 100% under these reaction conditions by varying the length of the reaction time, with longer reaction periods producing greater conversion percentages. It is preferred to retain some nitrile and ester functional groups to contribute to the robust mechanical properties of the resulting fiber adsorbent. Conversely, the greater the number of amide oxime substituents, the faster Pd adsorption occurs and the greater the loading. Therefore, one skilled in the art will be able to select an appropriate level of amide oximation to quantitatively determine the adsorption results.

[0025] As described, the resulting fibers substituted only with amide oximes (referred to herein as "A-fibers") were used in the following tests and were particularly effective at all concentrations of Pd in ​​acidic solutions. Additionally, fibers disubstituted with carboxylate amide oximes (referred to as "CA-fibers"), prepared as described subsequently in Example 2 below, can optionally be used to adsorb Pd from more highly concentrated solutions. As a group, A-fibers and CA-fibers are referred to as "substituted acrylic fibers."

[0026] Example 2: A first comparative fiber, CA-fiber, was prepared by reacting Orion acrylic fiber with a water / methanol solution of hydroxylamine as above, but for a period of time sufficient to replace only about 45% of the CN groups with amidoxime. Thereafter, the partially amidoximated fiber was treated with 1 M NaOH at room temperature for 8 to 24 hours to convert most of the remaining CN (about 85% of the remaining CN) groups to carboxylate ester groups. The resulting CA-fiber was carboxylated and amidoximated, with about 10% residual CN groups and ester groups.

[0027] Example 3: Second comparative, untreated fiber was Orion only, which has a natural complement of CN groups and some ester groups. This was the second comparative fiber, U-fiber, used in the tests described below to show that it did not adsorb Pd from an acidic solution.

[0028] Example 4: A test solution containing Pd was dissolved in a 0.1 M HCl solution to produce an acidic solution containing 20 ppm Pd. This high Pd concentration is similar to that of palladium electroless plating wastewater. The test described above was carried out at room temperature (22°C). The A-fiber was exposed to the test solution for a period of 2 hours. Figure 2 The time period shown graphically in . That is, Figure 2The diagram shows the adsorption rate of Pd. After the A-fiber was contacted with the test solution for about 40 minutes by gentle stirring (about 100 rpm) by a magnetic stirring bar, the adsorption of Pd by the A-fiber was close to the saturation value. The loading capacity is expressed as g Pd / kg fiber (or expressed as mole Pd / kg fiber), which is close to 250gPd / kg fiber. In the case of about 60% of CN converted to amide oxime, the Pd adsorption capacity further increases to a value of 330g Pd / kg fiber, and remains essentially constant beyond this conversion level. In the case of a higher degree of CN conversion to amide oxime, the fiber becomes less flexible and more rigid. Therefore, the preferred chelated amide oxime A-fiber of the present invention with high Pd adsorption capacity and good mechanical properties for multiple use cycles can be produced by reacting the original acrylic fiber with hydroxylamine in a water / methanol solution at 70°C for 45 minutes, resulting in about 35% to 65% of the CN groups being converted to amide oxime groups.

[0029] Recovery of Pd after adsorption: After exposing the A-fiber to the acidic Pd-containing solution, the adsorbed Pd can be eluted using a 0.5 M thiourea solution containing 0.3 M HCl at room temperature and recovered. Figure 3 The Pd elution rate in terms of elution efficiency percentage is graphically shown relative to the relationship of time. The elution rate is faster, showing that it is substantially fully recovered in about 10 minutes or less and gradually approaches 100% in 15 minutes to 20 minutes. After elution, the A-fiber is rinsed with water to remove thiourea, and the resulting clean fiber can be reused in multiple cycles of adsorption / elution recovery.

[0030] Multiple Cycle Use: Chelation Test A-fibers were repeatedly cycled through the adsorption and elution steps under the above conditions. Figure 4 The Pd adsorption obtained in five consecutive cycles is shown graphically, expressed as loading percentage versus cycle number. The results clearly show that the yield is relatively constant over time, varying only by about 2%, i.e. 99 ± 1%. This indicates that the amide oxime group is retained by the fiber, i.e. it is not significantly hydrolyzed away.

[0031] Example 5, direct comparison at low Pd concentration: The test A-fibers of the invention described in Example 1 above (amide-oximated fibers only with 1 / 2CN converted to amide-oxime) and the first comparative CA-fibers described in Example 2 above (carboxylated and amide-oximated fibers) were exposed to a test solution of added Pd at 500 parts per billion (ppb) of Pd in ​​0.1 M HCl. The results of Pd adsorption are shown in Figure 5 The results of Pd extraction are shown in Figure 5In the same period of time (120 minutes), the extraction efficiency of the A-fiber of Example 1 was about 95%, while for the carboxylate-amide oximated CA-fiber, the extraction efficiency of Example 2 was less than half, about 40%.

[0032] Example 6, direct comparison at high Pd concentration: The inventive test A-fiber described in Example 1 above (a 1 / 2CN converted to amide oxime-only amide oxime fiber) and the first comparative AC-fiber described in Example 2 above (carboxylated and amide oxime fiber) were exposed to an added Pd test solution of Example 4 having 20 parts per billion (ppb) of Pd in ​​0.1 M HCl. The results of the Pd extraction are shown in Figure 6 In the same period of time (120 minutes), the extraction efficiency of the A-fiber of Example 1 was nearly the same as that of the carboxylate-amide oximated AC-fiber of Example 2, while the amide oximated A-fiber alone outperformed the carboxylate-amide oximated CA-fiber, 80% versus 78%.

[0033] Example 7: Untreated fibers were exposed to the test solution of 20 ppm added Pd as described above in Example 4. The fibers were essentially incapable of absorbing Pd.

[0034] Example 8: Test A-Fibers were cut into short lengths (1 cm) and packed into a plastic column of about 1.6 cm inner diameter and 15 cm length, with glass wool placed at the top and bottom ends to retain the fiber material in the column. The amount of fiber was about 2 grams in weight and occupied a vertical height of 5.5 cm in a vertically oriented column with a total fiber volume of about 10 mL. A mother liquor containing 1 ppm Pd solution (in 0.1 M HCl at pH=1) was pumped into the column from the top of the column by a peristaltic pump at a flow rate of 20 mL per minute. After passing through the column, the lean solution was collected in a measuring cylinder at different intervals for residual Pd analysis. After 20 liters of 1 ppm Pd mother liquor passed through the column, no Pd was detected in the outlet solution (detection limit 5 ppb). Therefore, the Pd breakthrough point (where Pd starts to leak through the column) is at least 2,000 times the column bed volume (10 mL) of the fiber adsorbent. Alternatively, the chelating fiber can remain in the column for the elution and washing steps and subsequently be recycled through the adsorption step. This system setup provides a practical commercial Pd recovery process.

[0035] Discussion: Inventive Tests A - Carbon Fibers, Chelated Acrylic fibers substituted only with amidoxime are unexpectedly capable of adsorbing Pd at very high capacities (250 g to 340 g Pd / kg fiber) in acid solution over a wide range of Pd concentrations, and repeated cycles of adsorption / elution / cleaning / adsorption result in nearly 100% recovery of their full capacity. The rates of the adsorption and elution portions of the cycle are sufficiently rapid that one skilled in the art will recognize that a continuous Pd recovery process is entirely feasible. Additionally, the percentage of residual CN groups can be varied to provide fiber robustness for hundreds of cycles before replacement is required.

[0036] The first comparative CA-fiber with both amide oxime and carboxylate functional groups shows about the same Pd loading capacity as the test A-fiber, but only when the Pd concentration is high (20ppm) in 0.1M HCl solution. At low Pd concentrations below about 5ppm, the loading capacity of the CA-fiber is lower than that of the test-A-fiber. For example, at 500ppb, the Pd loading capacity of the test fiber is 3 times that of the first comparative CA-fiber. Although not wishing to be bound by theory, the performance reduction of the first comparative CA-fiber may be attributed to the formation of hydrogels by carboxylate functional groups, resulting in interference with Pd entering the amide oxime group, and thus reducing Pd adsorption on the amide oxime group. The interference of hydrogel formation is more prominent at low concentrations of metal ions, and thus results in a lower Pd adsorption capacity of the fiber.

[0037] Additionally, considering the protonation chemistry in acidic solutions, the inventive substituted acrylic fibers described in this application are capable of extracting other platinum group elements, including Au, Pt, Re, Ru, Rh, because they each form chelated negatively charged chloride complexes in hydrochloric acid solutions similar to Pd. Furthermore, because Cu is not extracted by acidic solutions (e.g., 0.1 M HCl) containing substituted acrylic fibers, Pd can be selectively extracted from acidic wastewater containing both Pd and Cu.

[0038] Practicality:

[0039] It is obvious that the inventive fibers and methods of the present application have broad applicability to the pollution control industry, that is, to recover heavy metals from industrial wastewaters. For example, the substituted acrylic fiber adsorption / elution technology of the present invention will have important applications in the recovery of precious metals from industrial wastewaters. Thus, in an industrial process for electrodeless deposition of Cu on printed circuit boards (PCBs), a palladium-containing hydrochloric acid solution is used as a catalyst for the Cu deposition process. Washing the PCBs after Cu deposition produces large amounts of wastewater containing extremely low concentrations of Pd (1 ppm or less) and Cu (10 ppm or less). The inventive substituted acrylic fibers and adsorption / elution processes described in the present application provide an effective, low-cost and robust system for recovering Pd from such industrial wastewaters. Therefore, the inventive substituted acrylic fibers and cyclic adsorption / elution processes of the present invention have significant potential for use as a new standard in the heavy metal recovery industry.

[0040] It should be understood that those skilled in the art may make various modifications within the scope of the invention without departing from the spirit of the invention and without undue experimentation. The invention is therefore defined broadly by the scope of the appended claims, including current and future equivalents thereof as far as the prior art permits and in view of this specification (if necessary), with full scope.

Claims

1. A method for removing multiple elements from an acidified hydrochloric acid aqueous solution containing negatively charged chloride complexes of platinum group elements, comprising contacting the acidified hydrochloric acid aqueous solution containing the multiple negatively charged chloride complexes of the multiple elements with a chelating fiber comprising an acrylic polymer having pendant CN groups substituted with amidoxime groups, to produce a structure comprising: wherein n is from 1000 to 100,000, R is selected from alkyl, substituted alkyl, cycloalkyl, heterocycloalkyl, aryl or heteroalkyl, the percentage of amide oxime groups replacing the CN groups of the original acrylic polymer as a percentage of the CN groups in the original acrylic polymer is in the range of 10% to 100%, and after the substitution with amide oxime, the percentage of nitrile and ester functional groups remaining in the fiber is selected to provide the chelated fiber with suitable mechanical properties for repeated adsorption and elution cycles.

2. The method of claim 1, wherein the plurality of amidoxime groups are present in a range of 30% to 65% of the plurality of CN groups in the acrylic polymer.

3. The process of claim 2, wherein some of the residual CN groups are converted into carboxylate groups by reaction with NaOH.

4. The method of claim 1, wherein the platinum group element is selected from Au, Pt, Re, Ru, Rh and Pd.

5. The method of claim 1, wherein the platinum group element is adsorbed onto the fiber and the platinum group element is removed from the fiber.

6. The method of claim 5, wherein the platinum group element is removed by elution.

7. The method of claim 6, wherein the platinum group element is eluted using an HCl-thiourea solution.

8. The method of claim 7, wherein after the PGE elution, the fiber is rinsed to clean the fiber and then re-exposed to the acidified aqueous solution containing the PGE chloride complex in at least one additional adsorption / elution cycle.

9. The method of claim 8, wherein the adsorption / elution cycle is implemented in a continuous process.

10. The method of claim 5, wherein the platinum group element is Pd.

11. The method of claim 4, wherein the loading of the fiber with the platinum group element after adsorption is about 100% of the amidoxime substituents.

12. The method of claim 6, wherein recovery of the platinum group element from the fiber after elution is about 100%.

13. The method of claim 8, wherein recovery of the platinum group element from the fiber over the plurality of cycles is in the range of 99 ± 1%.

14. The method of claim 11, wherein the platinum group element is Pd.

15. The method of claim 12, wherein the platinum group element is Pd.

16. The method of claim 7, wherein the chelating fiber is disposed in at least one column and the acidified hydrochloric acid solution containing the negatively charged chloride complexes of the plurality of PGEs is pumped through the column until breakthrough and the fiber is subsequently eluted to recover the adsorbed PGEs.

17. The method of claim 4, wherein the PGE is present in the acidified aqueous hydrochloric acid solution along with Cu ions, and the fiber preferentially adsorbs the PGE over rejecting Cu, thereby differentially removing the PGE in the presence of Cu.

Citation Information

Patent Citations

  • Surface-functionalized polyolefin fibers and their use in methods for extracting metal ions from liquid solutions

    US10391472B2

  • Separation method of palladium from silver electrolyte

    CN102329959A

  • Preparation method and using method for polyamino / amidoxim-modified multifunctional ion exchange fibers

    CN109289803A

  • Anidoxime fibre with chelate function, its synthesis process and its application

    CN1250828A

  • Method for separating / recovering platinum family metal

    CN1493706A